Rosai-Dorfman Disease: A Case Report - Halder, Amrita Lal; Mollah, Md Abid Hossain (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Rosai-Dorfman disease (RDD) is a type of sinus histiocytosis. It is a rare disease (1:200000), particularly in children and commonly presents with massive, painless and usually bilateral cervical lymphadenopathy along with fever and weight loss. Leukocytosis, elevated erythrocyte sedimentation rate and hypergammaglobulinemia are common. A definitive diagnosis can only be made by histological analysis of affected lymph nodes. Emperipolesis and a typical immunohistochemical pattern characterized by positivity for S-100 protein and CD68 antigen and negativity for CD1a antigen are diagnostic for RDD. Here we report a case of RDD occurring in a 10-month-old child with progressive cervical lymphadenopathy and persistent fever. Histopathological and immunohistochemistry studies of a lymph node biopsy established the diagnosis. A watchful follow-up resulted in the resolution of fever and lymphadenopathy. J Bangladesh Coll Phys Surg 2022; 40: 299-301